Occupational Health and Safety (K3) Risk Management Analysis on Building Construction Projects in Indonesia: Literature Review - Maddeppungeng, Andi; Asyiah, Siti; Intari, Dwi Esti; Putro, Miftha Adityo; Setiawati, Dwi Novi (Jurnal Fondasi, 2023)
The construction of building construction projects in Indonesia is inseparable from various risks related to work accidents, therefore risk management is very important for construction to prevent or minimize negative influences caused by an unexpected event. Since the announcement of covid-19 for the first time in 2020 until now, Indonesia is still experiencing the COVID-19 pandemic so large-scale social restrictions are imposed. This leads to restrictions on activities in the construction project environment. This study aims to analyze risk identification, risk assessment, and risk control contained in building construction projects in Indonesia. This research uses the systematic literature review method where data sources are obtained from "google scholar" in the form of published journals regarding occupational safety and health risk management in building construction projects in Indonesia from 2016-2021 with the keywords risk management, risk identification, risk assessment, risk control, and building construction. After the selection process, 23 journals were obtained. From this literature review, the most identified risks are technical project risks, the most emerging risk levels are moderate, and the most widely used risk control is administrative control.